Upaya Guru PAI dalam Menerapkan Situasi Belajar Mengajar dengan Metode Make a Match di Sekolah SMP Negeri 1 Mojoagung Kabupaten Jombang - Chotimah, Chusnul; Alfina, Tahta (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of this study was to determine the efforts of Islamic Religious Education teachers in applying the Make a match type cooperative learning method to the students of SMP Negeri 1 Mojoagung. This research is a qualitative research. The subjects in this study were all seventh grade students of SMP Negeri 1 Mojoagung. The process of applying the Make a Match type of cooperative learning method in the subject of Islamic Religious Education in class VII students of SMP Negeri 1 Mojoagung runs effectively and efficiently according to the steps that have been determined. In the steps of applying the make a match method, the researcher saw that the process was in accordance with the theory, and during the process of applying the students it was quite easy to be invited to work together to carry out the steps of the make a match method. This can be seen from the increase in student activity in participating in the learning process of Islamic Religious Education.